Rare case of urinary bladder agenesis - Multislice CT abdomen imaging - Indiran, Venkatraman (EduRad, 2013)
Complete agenesis of urinary bladder is an extremely rare anomaly with only a few live cases reported so far. In most of the instances death occurs early as it may be incompatible with life. Here we report a case of adolescent female with urinary bladder and unilateral renal agenesis, who presented with a rather unusual presentation of incontinence, for a computed tomography (CT) examination. Other congenital abnormalities visualised in the CT abdomen are also discussed.